Bridging Microbial Functional Traits With Localized Process Rates at Soil Interfaces - Blagodatskaya, Evgenia; Tarkka, Mika; Knief, Claudia; Koller, Robert; Peth, Stephan; Schmidt, Volker; Spielvogel, Sandra; Uteau, Daniel; Weber, Matthias; Razavi, Bahar S. (Frontiers in Microbiology, 2021)
In this review, we introduce microbially mediated soil processes, the players, their functional traits, and their link to the processes at biogeochemical interfaces (e.g., rhizosphere, detritusphere, (bio)-pores, and aggregate surfaces). A conceptual view emphasizes the central role of the rhizosphere in interactions with other biogeochemical interfaces considering biotic and abiotic dynamic drivers. We discuss an applicability of three groups of traits based on microbial physiology, activity state and genomic functional traits to reflect microbial growth in soil. The sensitivity and credibility of modern molecular approaches to estimate microbial specific growth rates demands further development. A link between functional traits determined by physiological (e.g., respiration, biomarkers) and genomic (e.g., genome size, number of ribosomal gene copies per genome, expression of catabolic versus biosynthetic genes) approaches is strongly affected by environmental conditions such as C and nutrients availability and ecosystem type. We address, therefore, the role of soil physico-chemical conditions and trophic interactions as drivers of microbially mediated soil processes at relevant scales for process localization. The strengths and weaknesses of current approaches (destructive, non-destructive and predictive) for assessing process localization and corresponding estimation of process rates are bridged to the challenges for modelling of microbially mediated processes in heterogeneous soil micro-habitats. Finally, we introduce a conceptual self-regulatory mechanism based on flexible structure of active microbial community. Microbial taxa best suited to each successional stage of substrate decomposition, become dominating and alter the community structure. The rates of decomposition of organic compounds, therefore, are dependent on functional traits of dominating taxa and microbial strategy, which are selected and driven by the local environment.